Horizontalists, verticalists, and structuralists: The theory of endogenous money reassessed - Thomas I. Palley (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2013)
This paper uses the occasion of the twenty-fifth anniversary of Basil Moore's book, Horizontalists and Verticalists, to reassess the theory of endogenous money. The paper distinguishes between horizontalists, verticalists, and structuralists. It argues Moore's horizontalist representation of endogenous money was an over-simplification that discarded important enduring insights from monetary theory. The structuralist approach to endogenous money retains the basic insight that the money supply is credit driven but remedies horizontalism's omissions and over-simplifications. Twenty-five years later, horizontalism has largely morphed into structuralism. The theoretical challenge going forward is to develop the role of money and finance in a Keynesian theory of output determination. As regards monetary policy, the challenge is how to conduct policy in a world of endogenous money. These concerns emanate naturally from a structuralist perspective on endogenous money.
urn:nbn:de:101:1-201403119904
Keywords: E4; E41; E43; E5; 330; Endogenous money; horizontalists; verticalists; strudturalists; monetarism; bank lending